On the effect of hippocampal c-Jun N-terminal kinase inhibition on object recognition memory - Rossato, Janine I.; Radiske, Andressa; Gonzalez, Maria Carolina; Bevilaqua, Lia R. M.; Cammarota, Martín (Frontiers in Behavioral Neuroscience, 2022)
c-Jun N-terminal kinase (JNK) phosphorylates the transcription factor c-Jun in response to stress stimuli and contributes to both hippocampal synaptic plasticity and memory processing in mammals. Object recognition memory (ORM) is essential for remembering facts and events. In rodents, ORM consolidation and reconsolidation require a functional hippocampus. However, the possible involvement of hippocampal JNK on ORM processing has not yet been studied. Here we show that when injected into dorsal CA1 5 min, but not 6 h, after training adult male rats in the novel object recognition learning task, the JNK inhibitor SP600125 impaired ORM for at least 7 d without affecting exploratory activity, short-term ORM retention, or the functional integrity of the hippocampus. SP600125 did not hinder ORM retention when given in CA1 after a memory reactivation session carried out 24 h post-training in the presence of the same two objects presented during the training session, but caused time-dependent amnesia when one of the objects presented at training was replaced by a different but behaviorally equivalent novel one. Taken together, our results indicate that hippocampal JNK activity is necessary for ORM consolidation and reconsolidation but not for ORM recall or short-term retention.